Is lipoprotein(a) measurement important for cardiovascular risk stratification in children and adolescents? - Marco Giussani; Antonina Orlando; Elena Tassistro; Erminio Torresani; Giulia Lieti; Ilenia Patti; Claudia Colombrita; Ilaria Bulgarelli; Laura Antolini; Gianfranco Parati; Simonetta Genovesi (BMC, 2024)
Abstract Background Elevated lipoprotein (Lp(a)) levels are associated with increased risk of atherosclerotic processes and cardiovascular events in adults. The amount of Lp(a) is mainly genetically determined. Therefore, it is important to identify individuals with elevated Lp(a) as early as possible, particularly if other cardiovascular risk factors are present. The purpose of the study was to investigate whether, in a population of children and adolescents already followed for the presence of one or more cardiovascular risk factors (elevated blood pressure (BP), and/or excess body weight, and/or dyslipidemia), the measurement of Lp(a) can be useful for better stratifying their risk profile. Methods In a sample of 195 children and adolescents, height, body weight, waist circumference and systolic (SBP) and diastolic (DBP) BP were measured. Body Mass Index (BMI) and SBP and DBP z-scores were calculated. Plasma Lp(a), total cholesterol, high-density lipoprotein (HDL), triglycerides, glucose, insulin, uric acid and creatinine were assessed. Low-density lipoprotein (LDL) cholesterol was calculated with the Friedewald formula. High Lp(a) was defined as ≥ 75 nmol/L and high LDL cholesterol as ≥ 3.37 mmol/L. Results Our sample of children and adolescents (54.4% males, mean age 11.5 years) had median LDL cholesterol and Lp(a) values equal to 2.54 (interquartile range, IQR: 2.07-3.06) mmol/L and 22 (IQR: 7.8-68.6) nmol/L respectively. 13.8% of children had LDL cholesterol ≥ 3.37 mmol/L and 22.6 Lp(a) values ≥ 75 nmol/L. Lp(a) values were higher in children of normal weight than in those with excess weight (p = 0.007), but the difference disappeared if normal weight children referred for dyslipidemia only were excluded from the analysis (p = 0.210). 69.4% of children had normal Lp(a) and LDL cholesterol values and only 6.2% showed both elevated Lp(a) and LDL cholesterol levels. However, 16.6% of the sample, despite having normal LDL cholesterol, had elevated Lp(a) values. Multivariable analyses showed a significant association of LDL cholesterol both with Lp(a) values, and with the presence of elevated Lp(a) levels. For each mmol/L increase in LDL cholesterol the risk of having an elevated Lp(a) value increased by 73%. There was an inverse correlation between BMI z-score and Lp(a). Neither BP z-scores, nor other biochemical parameters were associated with Lp(a). Conclusions In our population more than one out of five children had elevated Lp(a) values, and in about 17% of children elevated Lp(a) values were present in the absence of increased LDL cholesterol. Our results suggest that Lp(a) measurement can be useful to better define the cardiovascular risk profile in children and adolescents already followed for the presence of other cardiovascular risk factors such as elevated BP, excess body weight and high LDL cholesterol.